A Comparative Analysis of Budgeting Policies in Tourism Development: The Cases of Thailand and Indonesia - Shadu Satwika Wijaya; Slamet Rosyadi; Muhammad Yamin; Wahyuningrat Wahyuningrat; Fauzi Faisal Akbar; Agus Ganjar Runtiko; Sunee Hongwiset (Universitas Teuku Umar, 2026)
This study aims to compare tourism development in Thailand and Indonesia by analysing budgeting policies and governance arrangements across five dimensions: the role of universities, institutional design, governance model, budgetary policy, and development strategy. This issue is of particular significance, as budgeting policies constitute a pivotal instrument in reconciling macroeconomic stability with sectoral development; nevertheless, their implications for the tourism sector remain insufficiently examined within the comparative research literature. Using a comparative case study approach, this study employs thematic analysis of policy documents and qualitative interviews to generate in-depth insights. The findings demonstrate that tourism outcomes are shaped by budgetary orientation. This study advances comparative public policy scholarship by demonstrating how fiscal design enables or constrains sectoral governance capacity. In the case of Indonesia, a strong emphasis on macro-fiscal discipline engenders fragmented tourism financing structures alongside an adaptive Pentahelix model, wherein universities function as network mobilisers within a predominantly bottom-up strategic framework. In contrast, Thailand reflects a more institutionalised and state-led configuration, characterised by stable and protected tourism budgets anchored by the Tourism Authority of Thailand (TAT), with universities integrated as innovation nodes within a top-down, investment-driven paradigm. Overall, the study underscores budgeting policy as a critical determinant in shaping tourism governance configurations and development trajectories.